THE Complete Asian COOKBOOK - Solomon, Charmaine, (Hardie Grant Books, 2013)
A beautifully crafted and comprehensive cookbook series based on the most iconic and influential book on Asian cuisine. For generations, The Complete Asian Cookbook has been the most well-respected and authentic cookbook on Asian food. Since its publication in 1976, it has become one of the most iconic and influential cookbooks in publishing history, garnering a dedicated following worldwide. Now, for the first time, Charmaine Solomon's groundbreaking work has been divided into a series of six geographical regions, each with a complementary design so they may be collected as a set. Asian cuisine has a wonderful range of culinary delights that can be simple, complex, fiery, mild, and tantalizing. With page after page of beautiful, authentic Asian dishes, the recipes in The Complete Asian Cookbook series have been tested and re-tested to ensure the flavor and character of each dish is preserved. The labor-intensive traditional preparation methods have been cut back, making the recipes easy to follow for the home cook. Each book has an invaluable introduction to the food, culture, and cooking methods of the country as well as common ingredients. Learn to cook pork vindaloo, Thai green curry, crab with fresh Kampot peppercorns, steamed prawn dumplings, or delicious Peking duck. Filled with stunning food photography, The Complete Asian Cookbook series will guide you through the vast scope of Asian cuisine with authentic recipes that work every time. Start cooking tonight and dine abroad in the Asian country of your choice!